2022
DOI: 10.1038/s41420-022-01220-0
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of METTL16 disrupts learning and memory by reducing the stability of MAT2A mRNA

Abstract: N6-methyladenosine (m6A) is abundant in the mammalian brain and is considered to have a wide range of effects on learning and memory. Here, we found that the upregulated methyltransferase-like protein 16 (METTL16) in the hippocampal tissues of Morris water maze (MWM)-trained mice contributed to improved memory formation and hippocampal synaptic plasticity. Mechanismly, METTL16 promoted the expression of methionine adenosyltransferase 2A (MAT2A) by the m6A methylation of the MAT2A mRNA-3′UTR-end to increase its… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…To investigate whether m 6 A modification increases mRNA stability as previously reported (Zhang et al 2022a ), we conducted the mRNA stability using transcriptional repressor actinomycin D. The stability of p21 mRNA was significantly increased in DON-treated HT22 cells, and METTL3 knockdown significantly prevented DON-induced increase in p21 mRNA stability (Fig. 4 A).…”
Section: Resultssupporting
confidence: 51%
“…To investigate whether m 6 A modification increases mRNA stability as previously reported (Zhang et al 2022a ), we conducted the mRNA stability using transcriptional repressor actinomycin D. The stability of p21 mRNA was significantly increased in DON-treated HT22 cells, and METTL3 knockdown significantly prevented DON-induced increase in p21 mRNA stability (Fig. 4 A).…”
Section: Resultssupporting
confidence: 51%
“…METTL16, as a newly identified methyltransferase, was only reported to install m 6 A modifications on a few noncoding RNAs and pre-mRNAs in majorities of studies before 2018, such as MAT2A, U6 snRNA, and MALAT1 (Brown et al, 2016;Shima et al, 2017;Warda et al, 2017) but a subsequent study revealed that METTL16 could promote the translation of more than 4000 mRNA transcripts (Su et al, 2022) which implied that it had multiple undiscovered functions. Thereafter, multiple studies concentrated on the physiological function of METTL16 and discovered that it regulated the m 6 A modification on different mRNAs (Guo et al, 2022;Zhang et al, 2022Zhang et al, , 2023.…”
Section: Discussionmentioning
confidence: 99%